Using systematic data categorisation to quantify the types of data collected in clinical trials: the DataCat project - Crowley, E; Treweek, S; Banister, K; Breeman, S; Constable, L; Cotton, S; Duncan, A; El Feky, A; Gardner, H; Goodman, K; Lanz, D; McDonald, A; et al. (BMC, 2020)
Background: Data collection consumes a large proportion of clinical trial resources. Each data item requires time and effort for collection, processing and quality control procedures. In general, more data equals a heavier burden for trial staff and participants. It is also likely to increase costs. Knowing the types of data being collected, and in what proportion, will be helpful to ensure that limited trial resources and participant goodwill are used wisely.